Cancer-associated fibroblasts drive CXCL13 production in activated T cells via TGF-beta - O’Connor, Richard A.; Martinez, Begoña Roman; Koppensteiner, Lilian; Mathieson, Layla; Akram, Ahsan R. (Frontiers in Immunology, 2023)
Introduction: Tumour-reactive T cells producing the B-cell attractant chemokine CXCL13, in solid tumours, promote development of tertiary lymphoid structures (TLS) and are associated with improved prognosis and responsiveness to checkpoint immunotherapy. Cancer associated fibroblasts are the dominant stromal cell type in non-small cell lung cancer (NSCLC) where they colocalise with T cells and can influence T cell activation and exhaustion. We questioned whether CAF directly promote CXCL13-production during T cell activation.We characterised surface markers, cytokine production and transcription factor expression in CXCL13-producing T cells in NSCLC tumours and paired non-cancerous lung samples using flow cytometry. We then assessed the influence of human NSCLC-derived primary CAF lines on T cells from healthy donors and NSCLC patients during activation in vitro measuring CXCL13 production and expression of cell-surface markers and transcription factors by flow cytometry.Results: CAFs significantly increased the production of CXCL13 by both CD4 + and CD8 + T cells. CAFinduced CXCL13-producing cells lacked expression of CXCR5 and BCL6 and displayed a T peripheral helper cell (TPH) phenotype. Furthermore, we demonstrate CXCL13 production by T cells is induced by TGF- and limited by IL-2. CAF provide TGF- during T cell activation and reduce availability of IL-2 both directly (by reducing the capacity for IL-2 production) and indirectly, by expanding a population of activated Treg. Inhibition of TGF- signalling prevented both CAF-driven upregulation of CXCL13 and Treg expansion.Discussion: Promoting CXCL13 production represents a newly described immune-regulatory function of CAF with the potential to shape the immune infiltrate of the tumour microenvironment both by altering the effector-function of tumour infiltrating T-cells and their capacity to attract B cells and promote TLS formation.